INSTRUMENTS AND METHODS OF CONTROL OF THE CONCENTRATION OF PARAFIN IN OIL - R. S. Kashayev; O. V. Kozelkov; Z. S. Idiyatullin; A. N. Temnikov; E. N. Ozherelyeva; E. V. Perelevsky (Известия высших учебных заведений: Проблемы энергетики, 2017)
Made ananalysis of contemporary laboratory devices and methods of control and analysis of paraffin ’s concentration in oils and oil products. Obtined NMR-spectra of standard and natural oil samples. Made an analysis of spectra line parameters. Established correlations between paraffin ’s concentrations, densities and relaxation times. Suggested for aim of of express-analysis to use method of nuclear magnetic resonance relaxometry (NMRR) and Portable relaxometer NMR-NP1.